Penerapan Hak Cuti Bagi Pekerja Perempuan Pada Perusahaan Badan Usaha Milik Negara (BUMN): (Studi Di PT BTN Kantor Cabang Mataram) - Putu Mitha Alfiyana; Any Suryani Hamzah (Private Law, 2022)
This study aims to find out how to arrange leave rights for women workers according to labor laws and the implementation of women's leave rights according to labor laws against regulations at Bank BTN KC Mataram companies. Implementation of research using empirical research methods. Based on the results of the study, the rights of women workers to leave have been regulated in Law Number 13 of 2003 concerning Manpower. Bank BTN KC Mataram has an official bond agreement. Female workers get special leave rights in the form of leave for menstruation, pregnancy, childbirth, and miscarriage. This provision is regulated in the signing of the cooperation. The company should give special leave to all female workers regardless of whether the worker is in service or not.